Occupying and Expanding (un)Expected Categories: Ways of Being and Becoming Indigenous within the United Nations System (Alternautas, 2022)
This contribution is part of a project that seeks to understand the indigenous category through the participation of self-identified indigenous people in the context of several UN meetings. I will outline some unfinished reflections on how the analytical category 'indigenous' is represented within some spaces of the UN system. I will thereby explore how these representations fit with expected ideas of what it 'is to be indigenous' in these spaces, and how, through the observation of the performance of expected categories, the meanings of the indigenous category are expanded within a specific context and place.